2015
DOI: 10.1038/nn.3945
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and glutamatergic microdomains in a subset of rodent mesoaccumbens axons

Abstract: Mesoaccumbens fibers are thought to co-release dopamine and glutamate. However, the mechanism of co-release of dopamine and glutamate is unclear, and the co-release by mesoaccumbens fibers has not been documented. By electron microcopy we showed that some mesoaccumbens fibers have vesicular transporters for dopamine (VMAT2) in axon-segments continuous with axon-terminals that lack VMAT2, but contain vesicular glutamate transporters type 2 (VGluT2). In vivo overexpression of VMAT2 did not change segregation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
259
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(286 citation statements)
references
References 35 publications
19
259
0
Order By: Relevance
“…Similar D2 regulation in both hemispheres accompanied hemispherically equivalent release in the contralateral DMS, in contrast to D2 regulation of contralateral/ipsilateral VTA projections. Based on the confirmation of our findings using optogenetics, contralateral dopamine release is driven by dopamine neurons; however, optical activation does not preclude the effects of glutamate corelease (41), which may facilitate hemispherically equivalent release.…”
Section: Discussionsupporting
confidence: 65%
“…Similar D2 regulation in both hemispheres accompanied hemispherically equivalent release in the contralateral DMS, in contrast to D2 regulation of contralateral/ipsilateral VTA projections. Based on the confirmation of our findings using optogenetics, contralateral dopamine release is driven by dopamine neurons; however, optical activation does not preclude the effects of glutamate corelease (41), which may facilitate hemispherically equivalent release.…”
Section: Discussionsupporting
confidence: 65%
“…DA and glutamate are co-released from VTA DA neurons (21)(22)(23) and share several release properties (20). We observed that the M 5 mAChR-mediated potentiation affects oEPSCs recorded from spiny projection neurons in a similar fashion as oDA transients evoked by direct optogenetic stimulation of DA axonal projections (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…However, the degree of potentiation of oEPSCs by muscarinic agonists was significantly reduced in vGluT 2 -cre compared with DAT-cre mice, suggesting M 5 mAChRs activity preferentially regulates DA releasing neurons. Recently, Zhang et al (23) reported that dopaminergic and glutamatergic vesicular systems coexist, but segregate to different compartments of the same axonal projections. This observation raises the possibility that the number and/or coupling efficiency of M 5 mAChRs can be differentially expressed at these two compartments within the same axonal projection, favoring glutamate over DA transmission ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations